A Case Report of Pseudoxanthoma Elasticum-like Papillary Dermal Elastolysis - Jehad O. Hariri, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Pseudoxanthoma elasticum-like papillary dermal elastolysis is a relatively rare disorder within the literature. Increased awareness of this entity will broaden the differential diagnoses among dermatologists encountering such a condition. Pseudoxanthoma elasticum-like papillary dermal elastolysis tends to occur predominantly in elderly females. Clinically, the lesions present as papules and cobblestone plaques on the neck, resembling pseudoxanthoma elasticum. Histologically, there is absence of elastic fibers in the papillary dermis, and no calcification of the remaining fibers. Pseudoxanthoma elasticum-like papillary dermal elastolysis differs from Pseudoxanthoma elasticum by the absence of systemic manifestations, hence patients are reassured and no further workup is warranted. As of now, no effective treatments are available for this entity. Pseudoxanthoma elasticum-like papillary dermal elastolysis should be in the differential diagnosis of a dermatologist when encountering a clinical presentation of Pseudoxanthoma elasticum in an elderly patient localized to the neck, with absence of fragmented and calcified elastic fibers on histologic examination.